Economic Diplomacy and International Trade: ASEAN's Quest to Value‐Claim. (1st October 2012) - Selmier, W. Travis; Oh, Chang Hoon
Abstract Utilising economic diplomacy theory, this study specifies a statistical model to reveal ASEAN members' capacity to negotiate better international trade outcomes. Examining imports into ASEAN members from 134 nations between 1980 and 2001, we find that ASEAN's diplomats were able to pursue more 'value‐claiming' in economic diplomacy than expected. While our results support the commonly accepted view in economic diplomacy that smaller nations are pressured to accept trade outcomes desired by larger nations, we also find support for a new perspective: smaller nations obtain more favourable trade outcomes, as members of a regional trade bloc, which cannot be achieved as individual nations. We find that ASEAN's conversion to a fully fledged regional trade agreement in 1992 significantly enhanced this capacity. This study adds a different perspective to the substantial literature examining cases in trade and economic diplomacy.